Evaluasi Kesesuaian Lahan Kopi Robusta (Coffea canephora) Desa Pucaksari Kecamatan Busungbiu Kabupaten Buleleng Menggunakan Analisis Sistem Informasi Geografi - Silalahi, Agnes Verawaty; Rosyadi, R Ibnu (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2024)
Topographic and climatic factors support robusta coffee growing well in Indonesia. However, data from the Central Statistics Agency (BPS) shows that robusta coffee production has decreased over the last decade (2010–2019), especially in the Pucaksari Village area, Bali Province. This research aims to evaluate the suitability of robusta coffee land for each land unit in Pucaksari Village. This method applies the method of interpreting land use, slope, and soil type for further analysis using land evaluation methods and geographic information systems (GIS). The research results show that the land units K1L2Be and K1L3Be with slope characteristics between 8–30%, altitudes of 400–900 meters above sea level, and Eutric Cambisol soil types are included in the appropriate class (S2) for robusta coffee, with an area of 94,7% of the total area of the study area. Meanwhile, 5.23% of the land units K1L4Be area with a slope >30% is in the marginal class (S3). Land units K4L4Be with a slope >30% and a height of 0-300 meters above sea level has an unsuitable class (N). Robusta coffee production in Pucaksari Village can be increased by maintaining the quality of land in the S2 area and improving the quality of S3 land. For category (N) areas, a special study is needed as a reference or basis for planning the development of coffee plantations and mapping the development potential of other areas such as tropical rainforest tourism and agriculture.